Algoritmos non delayed relax-and-cut para o problema do caixeiro viajante assimétrico - Azevedo Junior, Hildebrando Barros de (2019)
The Traveling Salesman Problem (PCV) is one of the most studied problems in the literature, having applications in different areas such as logistics, robotics and transportation of materials and people. In this Work, we propose a Non Delayed-Relax-and-Cut (NDRC) algorithm for the Asymmetric Traveling Salesman Problem (PCVA), where unlike traditional Lagranian Relaxation algorithms, the exponential dualization of many inequalities is possible. As additional contributions, two heuristics are proposed for obtaining viable primal solutions. As well as valid inequality separation procedures for PCVA, in order to evaluate the impact caused by stronger Lagrangean limiters.